Model Perilaku Konsumen dalam Keputusan Pembelian Produk Agribisnis Ready-to-Eat Berbasis Pangan Lokal - Fitry Purnamasari; Andi Khaerun Niza; Ayu Saputri Bahar; Wardimansyah Ridwan (Universitas Negeri Makassar, 2026)
The advancement of digital technology has transformed consumer behavior in purchasing processes, including in the context of ready-to-eat agribusiness products based on local commodities. This study aims to analyze the influence of perceived ease of use, perceived usefulness, and trust on purchase decisions with attitude as a mediating variable among consumers in Makassar City. This research employed a quantitative approach using a survey method, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that perceived ease of use, perceived usefulness, and trust have positive and significant effects on attitude. Furthermore, attitude significantly influences purchase decisions. Trust is identified as the most dominant factor in shaping consumer attitudes. These findings highlight that trust in product quality and safety is a key determinant in driving purchase decisions, particularly for perishable ready-to-eat food products. In addition, the ease of use and usefulness of digital platforms contribute to forming positive consumer evaluations. This study provides practical implications for agribusiness actors to enhance consumer trust and optimize digital platforms in their marketing strategies.